Mix de óleos essenciais em dietas para juvenis de tilápia do Nilo: desempenho produtivo e bioquímica plasmática - Sosa, Bruno dos Santos (2018)
The objective of this study was to evaluate the inclusion of increasing levels of the commercial mix of cashew (Anacardium occidentale) and castor oil (Ricinus communis) essential oils as an additive in diets for Nile tilapia. For this purpose, 240 juveniles with initial weight of 35.06 ± 1.02 grams were distributed in a completely randomized design (four treatments and six replications) in 24 cylindrical-conical tanks and received for 60 days diets containing increasing levels of essential oil (0.10, 0.15; and 0.20%) and a control (without inclusion of the additive). After the experimental period the animals were euthanized with 250 mg L-1 of benzocaine to perform the analyzes of productive performance, carcass traits, centesimal composition and plasma biochemistry. There were no significant differences (P> 0.05) for the productive performance, carcass traits, centesimal composition and triglycerides composition, VLDL, total proteins, urea and glucose, and a significant difference (P<0,05) in the total cholesterol, HDL and LDL analyzes. The inclusion of commercial EO (Essential) did not interfere the productive performance of juvenile Nile tilapia. However, it had an improvement in the levels of transporter lipoproteins, increasing HDL levels and decreasing plasma LDL, which may be a justification for studies with higher doses of OE and different age groups in search of more answers regarding the bioactive capacity of the OE.